Pengaruh Diabetes Melitus Terhadap Tajam Penglihatan - Sudirman, Sudirman (Universitas Qamarul Huda Badaruddin, 2020)
Low vision affected by cataracts is also caused by retina disease. Diabetes is a disease that affects the retina. The population in the Kopang Health Center area has a low socioeconomic and education. The aim of this study was to evaluate the influence of diabetes mellitus on visual acuity. This study is non-experimental with a cross-sectional method and was carried out involving 73 respondents as sample aged 40 years, who were taken by simple random sampling in Kopang Primary Health Care, Central Lombok. Statistical analysis shows this study revealed that diabetes mellitus was significantly (P <0.05) influenced to visual acuity was equal to 42.5%, it mean that diabetes mellitus was found in 42.5% of those with low vision.